Analisis straregi pengembangan usaha UMKM olahan kerupuk “Aneuk Metuah” dalam meningkatkan kesejahteraan masyarakat dalam perspektif ekonomi Islam - YS, Tazkia Ayu Alharani; Jannah, Nurul; Aisyah, Siti (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
This research aims to analyze the business development strategy of MSMEs processed "Aneuk Metuah" crackers in order to improve community welfare from an Islamic economic perspective. This research was conducted in Batu Eight Hamlet, Rantau Pauh Village, Aceh Tamiang Regency. This research uses descriptive qualitative methods. Test the validity of the data using the triangulation method. Data collection techniques include observation, interviews and documentation. SWOT matrix analysis is used as an analytical approach. The SWOT analysis approach combines an assessment of the strengths, weaknesses, opportunities and threats of a project, identifying internal and external elements that contribute and do not contribute to achieving these goals. The research results show that the strategy for developing the MSME business for processed "Aneuk Metuah" crackers in improving community welfare includes the S-O strategy, namely increasing the standardization of MSME products and optimizing the availability of raw materials, the W-O strategy, namely increasing product creativity and innovation and improving production facilities and infrastructure, the S-T strategy, namely by increasing the productivity of MSMEs and increasing the competitiveness of MSME products as well as the W-T strategy, namely by increasing MSME cooperation and building a conducive business climate. Apart from that, the development of the "Aneuk Metuah" Cracker Processed MSME business must refer to and be in line with the Islamic economic perspective so that the business carried out will receive blessings in this world and the hereafter.